ENHANCE TENTH GRADE STUDENTS' READING COMPREHENSION OF NARRATIVE TEXT USING GOOGLE PLAY BOOKS - Anita Anggraeni; Della Hellena (IKIP Siliwangi, 2023)
This study looked into how well tenth-grade students' reading comprehension of narrative texts was improved by Google Play Books. The researchers also looked into the challenges that teachers and students encountered when utilizing Google Play Books in the classroom. A mixed-methods approach with an explanatory design was used in the study. Twenty students from a private high school in Batujajar who were in the tenth grade took part in the study. Through experiments, observations, questionnaires, and field notes, the researchers gathered data. The findings demonstrated how well Google Play Books works to increase readers' understanding of narrative text. Both students and teachers found the software to be helpful in the learning process. The program was not very difficult for the teachers to use, although they did run into some errors and issues while using it on some students' iPhones. Additionally, the students encountered certain practical and technological challenges when using Google Play Books, including signal issues, internet data utilization, and app satisfaction. According to the study's findings, teachers can successfully teach reading comprehension in narrative literature in the classroom by utilizing Google Play Books. However, in terms of technical concerns and selecting an interesting story, teachers need to be more prepared.